Thermo acoustic tiles performance in small-scale sheds for laying hens - Moreira da Silva, Brayam [UNESP]; Mollo Neto, Mario [UNESP]; Sartori, Diogo de Lucca [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2022)
Climate change significantly affects the welfare and productivity of laying hens. In this research, the thermal performance of three different roofs for sheds composed of ceramic, fibre cement, and thermoacoustic tiles was analysed with the objective of verifying the performance and the levels of thermal comfort of the different roofs, observing the conditions of thermal comfort inside the environment of the sheds. The internal environment was monitored by dataloggers and sensors, which collected data on air temperature, black globe temperature, and relative humidity from February to March 2020. Data from the internal environment of the facilities were used to calculate comfort indexes for laying hens. With the results, the best observed performance for black globe, temperature, and humidity index (BGTH), and the effective temperature index (ETI) was that of the ceramic tile. The thermoacoustic tile presented a lower performance for the temperature and humidity index (THI), when compared to the others. No significant differences were observed for the thermal radiation load (TRL) between the evaluated tiles, and with these results it was possible to conclude that the ceramic tile presented the best thermal performance compared to the other evaluated kinds.
Keywords: Comfort; Comfort Index; Coverage; Poultry; Sensors; System Dynamics